ESTIMATION OF PRIMARY METABOLITES FROM VARIOUS PARTS OF TERMINALIA CHEBULA RETZ. - ARCHANA SHARMA,; SUCHITRA MEENA,; NACHIKETA BARMAN, (The Bioscan, 2011)
In the present study the biochemical evaluation of primary metabolites (total soluble sugars, starch, lipids, proteins and phenols) from Terminalia chebula has been carried out from various parts viz., leaves, stems, seeds and fruits. The various plant parts of T. chebula varied in composition of primary metabolites. The leaves of T. chebula showed maximum content of sugar (6.65 mg/gdw), starch (7.12 mg/gdw) and protein (44.40 mg/ gdw). Lipids were higher in fruits (72.20 mg/gdw) while the phenol content was maximum in seeds of T. chebula (72.46 mg/gdw).